(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The antibiogram is useful for tracking trends in antimicrobial resistance over time, including information specific to an ICU or ward or comparing inpatients and outpatients. A cumulative antibiogram will be compiled for our institution as part of our antibiotic stewardship programme.This prospective study was conducted by the Department of Microbiology, Santosh Medical College & Hospital, Ghaziabad, Uttar Pradesh from January to December 2021. The organisms and their susceptibility patterns were collected and cumulative antibiograms were prepared. A total of 1395 specimens were received in the Microbiology laboratory from various departments of Santosh Hospital, Ghaziabad, for culture and sensitivity; 450(32.2%) samples yielded a positive culture, whereas 945(67.7%) samples yielded no growth. It is crucial to try everything possible to choose wisely. Antibiotics balance the need for a broad spectrum of empiric coverage of potential microorganisms with the need to preserve effective available antibiotics when they are absolutely necessary.